Hubungan Antara Kematangan Emosi Dengan Prokrastinasi Dalam Penyusunan Skripsi Mahasiswa Fakultas Psikologi Universitas Muhammadiyah Surakarta - Habibah, Dinda Prihandika Nur, Siti Nurina Hakim, S.Psi., M.Si., Psi (2017)
The purpose of this study was to determine relationship the Emotional Maturity with Procrastination Of Student College Preparing Thesis in Muhammadiyah University of Surakarta. The hypothesis is a negative relationship between Emotional Maturity with Procrastination Of Student College Preparing Thesis in Muhammadiyah University of Surakarta. Subjects in this study were 80 student. The population used in this study were student college of psychology faculty batch 2006 until 2012 Muhammadiyah University Of Surakarta and reparing thesis at least one year or two semesters. The measuring instruments used in this study are: a) Scale Emotional Maturity and b) Scale Procrastiation. Data analysis chniques used in this study is the product moment correlation, but because it is not linear then using Spearman's nonparametric statistical techniques. Conclusion ypothesisofnorelationship between Emotional Maturity With Procrastination Of College Student Preparing Thesis In Muhammadiyah University Of Surakarta. This is indicated by the value of r = -0.105 with sig. 0,178; (p>0.05), it means researchers hypothesis is rejected. Emotional Maturity level is high while level of Procrastination in preparation of thesis is classified. This is demonstrated by the empirical mean (RE) of Emotional Maturity 78,58 and the average hypothetical (RH) 65 while empirical mean (RE) Procrastination Of College Student Preparing Thesis is 57,01 and average hypothetical is 62,5.